Protective Effect of Carbon Dots Derived from Salvia miltiorrhiza Pretreatment in Acute Myocardial Infarction in Rats - Liyang Dong; Menghan Li; Tianyou Cao; Yafang Zhao; Shuxian Wang; Peng Zou; Yue Zhang; Huihua Qu; Yan Zhao; Hui Kong (Nanomaterials, 2025)
Acute myocardial infarction is an ischemic injury of the myocardium caused by an imbalance in the blood supply to myocardial tissues, which poses a serious threat to human life and health. Oxidative stress has been recognized as a significant contributor to acute myocardial infarction. Salvia miltiorrhiza Carbonisata (SMC) is among the most frequently employed herbal remedies for the treatment of acute myocardial infarction; however, the exact identity of its principal active constituents is not well defined. Research indicates that carbon dots (CDs) exhibit significant biological properties. Consequently, we initially synthesized carbon dots (CDs) from Salvia miltiorrhiza Carbonisata, with the objective of exploring how SMC-CDs mitigate isoproterenol (ISO)-induced myocardial infarction (MI) in rats. The results showed that the pretreatment with SMC-CDs markedly enhanced compromised cardiac function, mitigated myocardial fibrosis and the infiltration of inflammatory cells, decreased the size of the infarct, and suppressed cardiomyocyte apoptosis. Furthermore, the antioxidant properties of myocardial tissue were enhanced, and oxidative stress caused by free radicals was effectively mitigated by SMC-CDs, which succeeded in reducing levels of myocardial enzymes and elevating the activity of relevant ATPases. This implies that SMC-CDs could be a potential candidate for novel nanomedicine strategies designed to address cardiovascular ailments.